344 Interval Ultrasound Scanning in Idiopathic Pancreatitis - Are We Following Up Patients Appropriately?. (28th February 2022) - Pringle, H.; Ghandour, O.; Okocha, M.
Abstract: Aim: Acute pancreatitis of unknown cause requires investigation to identify reversible causes of the disease before classifying it as truly idiopathic. This study reports on the follow-up of patients in a district general hospital (DGH) who were diagnosed with acute pancreatitis of unknown cause compared to the gold standard evaluation of the disease by interval abdominal ultrasound scan (US) or outpatient endoscopic US. Method: Inclusion criteria was all patients discharged from the DGH with a diagnosis of acute pancreatitis and no cause described on the discharge summary from 1st January 2021 to 30th June 2021. The primary outcome was outpatient abdominal US follow-up. Secondary outcomes included an endoscopic US booked as an outpatient. Patients with gallstones identified on imaging or with another identified cause of the acute pancreatitis were excluded. Results: 50% (12 out of 24) patients did not receive follow-up US or any other imaging. Of the patients who did receive follow-up imaging 50% (6 out of 12) had a magnetic resonance imaging (MRI) abdomen or magnetic resonance cholangiopancreatography (MRCP) and the remainder 50% had an abdominal US. 12.5% of patients (3 out of 24) had an outpatient endoscopic US requested. Conclusions: Management of patients with acute pancreatitis is costly at an estimated £303 per night. To reduce likelihood of future unnecessary admissions, patients require appropriate investigation to have any reversible causes identified and managed. In a system which has suffered bed shortages and significant financial restraints we need to ensure these patients are not lost to US follow-up.